Employee Engagement Culture and Positive Work Behavior as Drivers of Organizational Success: A Systematic Literature Review - Nur Atika Yuniarti; Puji Setya Sunarka; Ryan Arya P; Atika Mutiarachim; Fika Ulfa W (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The study purpose of the research is to analyze the role of employee engagement culture in fostering positive work behavior and increasing organizational success. Employee engagement has become a human resource phenomenon in organizations in a dynamic business environment in the era of digital transformation. Employee involvement is not only an individual psychological state, but a very strong attachment to organizational culture and forms positive work behavior so that it can increase organizational success. However, previous studies still found several gaps, namely employee engagement and positive work behavior separately without providing an integrative understanding of how an engagement-oriented culture translates into sustainable organizational results. Materials and methods. Used a Systematic Literature Review (SLR) with the PRISMA framework, 38 peer-reviewed articles indexed in Scopus and accredited by Sinta, published between 2022 and 2025. Results. Employee engagement culture is strategic organizational resource, positive work behavior was a mediating role to increase organizational success, and organizational success must applied human resource performance, innovation, sustainability, and employee well-being. Conclusions. This study contributes to develop conceptual framework of engagement culture, positive work behavior, and organizational success. This research provides practice literacy for managers and policymakers to design inclusive, trust-based, and adaptive engagement strategies. Future research is proposed for empirical testing across sectors and cultural contexts.